Properties of UV-Curable Bisphenol-A Glycerolate Diacrylate Coatings_x000D_ Containing 1H,1H,2H,2H-Perfluorodecyl Acrylate Monomer - AKIN, EMRE; ÇAKIR, MUSTAFA (My University, 2018)
Abstract: In this study, fluorine chains were bonded with covalently in epoxy acrylate system via UV light.For this purpose, five different coating samples prepared. Bisphenol-A glycerolate diacrylate (epoxy acrylate)and 1,6-Hexanediol diacrylate were used as the main coating solution. The weight ratio of Bisphenol-Aglycerolate diacrylate and HDDA was determined as 7/3. As a long fluorine chain, 1H,1H,2H,2Hperfluorodecyl acrylate (PFOA) was added into the main coating solution in the ratios of 0.25 wt %, 0.50 wt%, 0.75 wt % and 1 wt %. All prepared solutions were coated on aluminum plates by 75 µm by wire woundapplicator and then cured via UV dryer. Physical properties of coatings were measured by tests such as MEKrubbing test for solvent resistance, gloss 60otest for brightness, cross-cut test for adhesion property and pencilhardness test for scratch resistance. Hydrophobicity was measured as static water contact angle test. The totalsurface energy was calculated by contact angle measurement software. In terms of mechanical properties,sheen impact test (for coating samples) and Shore - D hardness tests (for free film samples) were carried out.By examining the results of all these tests; cross-cut adhesion and gloss 60ovalues decrease with the fluorinecontent. On the other hand, by the increasing within the content of the fluorine chains, Taber abrasionresistance and hydrophobicity increase significantly but sheen impact resistance and Shore - D hardnessvalues decrease slightly. In terms of cost and overall results, the most proper and multifunctional coatingseemed at 0.25 wt %.

Özet : Bu çalışmada flor zincirleri, UV ışığı ile sertleşebilen epoksi akrilat sistemine kovalent olarak_x000D_ bağlandı. Bu amaçla beş farklı kaplama örneği hazırlanmıştır. Ana kaplama çözeltisi olarak Bisfenol-A_x000D_ gliserolat diakrilat (epoksiakrilat) ve 1,6-Heksandiol diakrilat kullanıldı. Bisfenol-A gliserolat diakrilat ve_x000D_ HDDA'nın ağırlık oranı 7/3 olarak belirlendi. Uzun bir flor zinciri olarak 1H, 1H, 2H, 2H-perflorodesil_x000D_ akrilat (PFOA) ağırlıkça % 0.25, % 0.50, % 0.75 ve % 1 oranlarında ana kaplama çözeltisi içine ilave_x000D_ edildi. Hazırlanan tüm çözeltiler, alüminyum plakalar üzerinde 75 µm tel sargılı aplikatör ile kaplandı ve_x000D_ daha sonra UV kurutucu ile sertleştirildi. Kaplamaların fiziksel özellikleri; solvent direnci MEK ovma_x000D_ testiyle, parlaklık 60o_x000D_ parlaklık ölçüm testiyle, çizilme direnci kalem sertliği testiyle, yapışma özelliği_x000D_ çapraz-kesme testiyle yapılmıştır. Yüzeylerin hidrofob özelliği statik su temas açısı testiyle ölçüldü. Toplam_x000D_ yüzey enerjisi temas açısı ölçüm yazılımı ile hesaplandı. Mekanik özellikler açısından, Sheen darbe testi_x000D_ (kaplama numuneleri için) ve Shore-D sertlik testleri (serbest film numuneleri için) yapıldı. Bu testlerin_x000D_ sonuçları ele alındığında, çapraz kesme-yapışma ve parlaklık 60o değerleri flor içeriğinin artması ile azaldığı_x000D_ gözlemlendi. Diğer taraftan Taber aşınma direnci ve hidrofobisite önemli ölçüde artmaktadır, ancak_x000D_ darbelere karşı dayanıklılık ve Shore-D sertlik değerleri azalmıştır. Maliyet ve genel sonuçlar açışından_x000D_ bakıldığında en uygun ve çok fonksiyonlu kaplama % 0.25 olduğu bulunmuştur.
1H, 1H, 2H, 2H-Perflorodesil Akrilat Monomeri İçeren UV ile Sertleşebilen Bisfenol – A Gliserolat Diakrilat Kaplamalarının Özellikleri